Real world utilization of EGFR TKIs and prognostic factors for survival in NSCLC during 2010–2016 in Sweden: A nationwide observational study. Issue 9 (12th August 2019) - Bergqvist, Michael; Christensen, Helene N.; Wiklund, Fredrik; Bergström, Stefan
Abstract : The purpose of our study was to investigate time trends in treatment pattern and prognostic factors for overall survival (OS) in epidermal growth factor receptor (EGFR) targeting tyrosine kinase inhibitors (TKIs) treated nonsmall cell lung cancer (NSCLC) patients. Utilizing Swedish nationwide registers, we identified all Stage IIIB–IV NSCLC patients treated with EGFR TKIs and followed them from diagnosis (2010–2015) until death or end of observation (2016). Multivariable Cox regression analyses were performed to test associations of patient‐, tumor‐related factors with OS. Of 9, 992 Stage IIIB–IV NSCLC patients, the 1, 419 (14%) who initiated EGFR TKI treatment during observation were younger (median age 68 vs . 71 years), less ≥1 comorbidities (34% vs . 46%), more often female (59% vs . 47%), Stage IV (89% vs . 85%) and adenocarcinoma (85% vs . 66%) compared to non‐TKI treated patients. After TKI initiation, 7% ( n = 100) of the patients switched, 4% ( n = 62) rechallenged a TKI treatment, 65% ( n = 919) discontinued and 24% ( n = 338) had died. A more recent diagnosis demonstrated shorter time to EGFR TKI initiation, prolonged treatment length and longer median OS (15.3 months 2010–2011; 14.4 months 2012–2013; 18.6 months 2014–2015). Prognostic factors for longer OS when treated with EGFR TKIs were younger age, adenocarcinoma, less advanced clinical stage and less comorbid disease. In conclusion, during the observation period, survival improved for EGFR TKI treated NSCLC patients, as did the accessibility for targeted therapies for these patients. Abstract : What's new? In non‐small cell lung cancer (NSCLC), have treatment results with EGFR TKIs improved over time? In this study, the authors found that the answer is yes. Patients with a more recent diagnosis had a shorter time to initiation of treatment, prolonged treatment durations, and longer overall survival (OS) compared to patients diagnosed in earlier years. Prognostic factors for longer OS included younger age, adenocarcinoma, earlier clinical stage, and less comorbid disease. In view of targeted therapy options for EGFR‐related tumors, further understanding regarding real‐world utilization of contemporary treatment is needed.